Why Gametes are not Like Enriched Uranium. (15th September 2016) - Botterell, Andrew
Abstract: According to Rivka Weinberg, gametes are like enriched uranium: both are hazardous materials. Exposing human beings to enriched uranium can result in radioactivity and decreased life expectancy, while exposing sperm and ova to each other can result in the creation of needy innocent persons with full moral status. Weinberg argues that when we engage in activities that put our gametes at risk of joining with others and growing into persons, we assume the costs of that risky activity. She calls this the Hazmat Theory of parental responsibility. The theory is novel and important, and has far‐reaching consequences for the ethics of procreation, parenting, and population, implying among other things that that the only way to avoid acquiring parental responsibilities may be to "abstain from sexual intercourse or surgically interfere with our gamete‐release system." For these reasons the theory merits careful scrutiny. In this article I criticize the theory's account of how parental responsibility is acquired and its treatment of the standard of care expected of gamete possessors, and argue that it fails to properly account for a distinction between procreative costs and parental responsibility. Even if gametes are hazardous, it does not follow that parental responsibility in Weinberg's sense is acquired whenever one brings new persons into existence.